Evolution of Interdisciplinary Settings in the Study of the Structure of Rational Activity - O. D. Shipunova; I. P. Berezovskay; A. A. Lisenkova (Дискурс, 2024)
Introduction. The article is devoted to the philosophical analysis of the development of the instrumental structure of rational activity, taking into account the dynamics of the relationship between person and machine in the context of the intensification of industrial production in the second half of the 20th century and the transformations of subjective interactions in the digital environment. The authors consider rational activity in its specifically human function of a meaningful and transformative attitude to the life world, which is correlated in the social aspect with the instrumental support of productive labor.Methodology and sources. The study of the structure of activity is carried out within the framework of a systematic approach using the historical-genetic method in the description of the conceptual development of ergonomics, which marked the beginning of an interdisciplinary synthesis in the development of knowledge about the structure of rational activity on the basis of an anthropological attitude in the design of modern technologies. The cognitive perspective of the system approach to the analysis of the structure of rational activity makes it possible to combine in a single concept a wide range of factors that motivate and regulate the individual abilities of a person as a real subject of action in combination with information databases and specific conditions that include them in the cognitive network of cognition and social interactions.Results and discussion. The interdisciplinary attitudes of engineering psychology, the problem of the subject in the organization of an interactive digital space of rational activity are considered. The characteristics of the machine-centric and anthropocentric paradigms of designing human-machine interactions are presented. The transition to interdisciplinary attitudes of human ecology, taking into account the basic importance of the environment in these interactions, as well as to the attitudes of digital ecology in the design of the sphere of virtual interactions, is highlighted.Conclusion. The study of cognitive attitudes in the development of ergonomics shows the origins of the interdisciplinary approach to the analysis of the structure of rational activity and its increasing relevance due to the need to conceptualize engineering knowledge, taking into account the sociotechnical, human-dimensional nature of modern innovative projects in all spheres of activity.